Theoretically estimating the acoustic intensity of high-intensity focused ultrasound (HIFU) using infrared thermography - Zhou, Yufeng (2022)
High-intensity focused ultrasound (HIFU) has been used successfully in clinics for the treatment of a variety of cancerous and benign tumors. Characterization of the focused acoustic field is of importance in the planning of the ablation procedure and further development of HIFU technology. Quantitative estimation of acoustic intensity is feasible using the infrared (IR) thermography on an absorber. However, the current approach is limited to low power output. In this study, a theoretical model was established to describe the acoustic field and absorbed energy in the absorber with the presence of harmonics in the HIFU pressure waveform at the focus and then to calculate the temperature elevations during the HIFU heating, from which the acoustic intensities could be derived. The absolute difference between the derived and incident acoustic intensities in a 2-mm absorber at the varied acoustic power output (up to 80 W) and attenuation of the absorber (up to 346 Np/m/MHz) is <6%. In addition, the proposed approach was found to also work well for the absorber with a varied thickness because of the monotonic decrease of the temperature elevation. The effects of pulse duration and duty cycle of pulsed HIFU ablation on the estimation accuracy were also investigated. It is found that the estimation accuracy is good for short pulse duration using the equivalent acoustic intensity. Overall, the proposed approach could estimate the acoustic intensity and harmonic distribution of HIFU at the high power output using IR thermography for a large parametric range of absorber and HIFU output in the numerical investigation.